2015
DOI: 10.1371/journal.pone.0124817
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cardiovascular Disease Risk Factor Prevalence and Estimated 10-Year Cardiovascular Risk Scores in a Large Untreated French Urban Population: The CARVAR 92 Study

Abstract: BackgroundSurveys measuring effectiveness of public awareness campaigns in reducing cardiovascular disease (CVD) incidence have yielded equivocal findings. The aim of this study was to describe cardiovascular risk factors (CVRFs) changes over the years in an untreated population-based study.MethodsBetween 2007 and 2012, we conducted a screening campaign for CVRFs in men aged 40 to 65 yrs and women aged 50 to 70 yrs in the western suburbs of Paris. Data were complete for 20,324 participants of which 14,709 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…One strength of our study was the control of biases. At baseline, the HTA prevalence in CSs and COPD patients was similar to that observed in the general population 35 and large cohorts. 2 , 23 Although HTA was more prevalent in COPD patients, resting BP was not different between groups.…”
Section: Discussionsupporting
confidence: 77%
“…One strength of our study was the control of biases. At baseline, the HTA prevalence in CSs and COPD patients was similar to that observed in the general population 35 and large cohorts. 2 , 23 Although HTA was more prevalent in COPD patients, resting BP was not different between groups.…”
Section: Discussionsupporting
confidence: 77%
“…42 Although, in recent years, there has been a decrease in the number of active smokers, still about 15-20% of the population in developed countries are active smokers. 28,29,32,[43][44][45][46][47] This was confirmed by the results of own study. Most likely, the reduction in the percentage of smokers in the European Union was influenced by the introduction of laws prohibiting smoking in public places.…”
Section: Discussionsupporting
confidence: 71%
“…49 In contrast, the study in France showed that only 1% of respondents was characterized by a 5% or greater 10-year risk of CVD death. 44 This is probably related to the effective prevention of risk factors for CVD (decrease in the number of smokers and those suffering from HTN). Therefore, over 6 years (2007-2012), a decrease in the 10-year risk of CVD death in both men and women was observed.…”
Section: Discussionmentioning
confidence: 99%
“…3 The likelihood of someone developing a cardiovascular event depends on a combination of risk factors (RFs) rather than the presence of one RF 4 : the Framingham Risk Score (FRS) is a gender-specific algorithm used to estimate the 10-year cardiovascular risk (CVR) of an individual and classifies patients into low- (<10%), intermediate- (10%–20%), and high (>20%)-risk groups. 5 , 6…”
Section: Introductionmentioning
confidence: 99%